ON A COLLECTION OF ORTHOPTERA (INSECTA) FROM BARNAWAPARA WILDLIFE SANCTUARY, RAIPUR, CHHATTISGARH, INDIA - GUPTA, SUNIL KUMAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
The paper deals with the collection of Orthoptera fauna of Barnawapara Wildlife Sanctuary, Raipur, Chhattisgarh, which includes the study of 73 species pertaining to 62 genera under 8 families. Of these, eleven species i.e. Hieroglyphus indicus Mason, Oxya japonica japonica (Thunberg). Atractomorpha burri Bolivar, Loxoblemmus fletcheri Chopard, Holochlora indica Kirby, Khaoyaiana nitens Ingrisch, Hexacentrus unicolor Serville, Parasanaa donovani (Donovon), Phyllozelus (Phyllozelus) siccus siccus (Walker), Sanaa regalis (Brunner) and Sathrophyllia femorata (Fabricius) are recorded for the first time from Chhattisgarh state and one species Acrida turrita (Linnaeus) is new addition to the fauna of India.